Histopathology Is Key to Interpreting Multiplex Molecular Test Results From Postmortem Minimally Invasive Tissue Samples. (15th December 2021) - Ritter, Jana M; Seixas, Josilene N; Walong, Edwin; Dawa, Jeanette; Onyango, Clayton; Pimenta, Fabiana C; da Gloria Carvalho, Maria; Silva-Flannery, Luciana; Jenkinson, Tiffany; Howard, Katie; Bhatnagar, Julu; Diaz, Maureen; et al.
Abstract: Background: Minimally invasive tissue sampling (MITS) is an alternative to complete autopsy for determining causes of death. Multiplex molecular testing performed on MITS specimens poses challenges of interpretation, due to high sensitivity and indiscriminate detection of pathogenic, commensal, or contaminating microorganisms. Methods: MITS was performed on 20 deceased children with respiratory illness, at 10 timepoints up to 88 hours postmortem. Samples were evaluated by multiplex molecular testing on fresh tissues by TaqMan® Array Card (TAC) and by histopathology, special stains, immunohistochemistry (IHC), and molecular testing (PCR) on formalin-fixed, paraffin-embedded (FFPE) tissues. Results were correlated to determine overall pathologic and etiologic diagnoses and to guide interpretation of TAC results. Results: MITS specimens collected up to 3 days postmortem were adequate for histopathologic evaluation and testing. Seven different etiologic agents were detected by TAC in 10 cases. Three cases had etiologic agents detected by FFPE or other methods and not TAC; 2 were agents not present on TAC, and 2 were streptococci that may have been species other than those present on TAC. Result agreement was 43% for TAC and IHC or PCR, and 69% for IHC and PCR. Extraneous TAC results were common, especially when aspiration was present. Conclusions: TAC can be performed on MITS up to 3 days after death with refrigeration and provides a sensitive method for detection of pathogens but requires careful interpretation in the context of clinicoepidemiologic and histopathologic findings. Interpretation of all diagnostic tests in aggregate to establish overall case diagnoses maximizes the utility of TAC in MITS.